Smart fertilizer mixer system for fertigation - Roshahliza, M. Ramli; Mortaza, Mohamed; Nasrul Rahman, Abdullah (Institute of Electrical and Electronics Engineers Inc., 2022)
In modern agriculture, the fertigation technique is widely used to grow healthy crops and achieve quality yields. It involves mixing fertilizer into the water supply, typically referred to as the irrigation system, for crop cultivation. In the case of manually mixed fertilizer, the challenge lies in determining the appropriate level of electrical conductivity (EC) of the mixture. High EC value will reduce the chance of survival in young plants, whereas low EC value could reduce the yield of matured plants. This paper intends to address the situation by proposing an automated nutrient solution mixing method that matches the required EC level. As part of the research setup, this study makes use of a systematic fertilizer mixer that carries out the fertilization system and the irrigation system concurrently. The stock solution of this fertigation system is a type of liquid fertilizer that, when dissolved in water, produces the positively charged Mg (+2) ions and the negatively charged SO4 ions (-2) thus making it possible to get an EC reading. Through this uncomplicated and economical method, farmers can confidently rely on EC sensors to check the concentration level of the mixed nutrition solution on their behalf.